Donald E. Pease, The New American Exceptionalism (Altre Modernità, 2011)
Donald E. Pease, The New American Exceptionalism(Minneapolis-London, University of Minnesota Press, 2009, pp. 246 ISBN 9780816627837)di Cinzia Scarpino